Exploring Management Practices in the Hospitality Industry: A Comprehensive Employee Perspective - Shrestha, Alina; Shrestha, Jeet (International Journal of Atharva, 2024)
This study explores management practices within the hospitality industry from the perspective of employees, focusing on various aspects of management effectiveness and employee engagement. A questionnaire survey was conducted among employees from different hospitality establishments, revealing a significant gender disparity in representation, with 75.4% male and 26.6% female respondents. Key findings indicate a strong consensus among participants regarding the importance of quality management practices, with a majority supporting new management styles aimed at enhancing quality across departments. Senior executives were generally perceived as effective communicators of company policies, with 53% of respondents expressing agreement on this matter. Furthermore, a notable percentage (76.1%) of employees acknowledged the responsibility of top management in ensuring quality performance. Leadership capability among managers was deemed essential, with 51.5% of participants strongly agreeing on its significance. Continuous self-improvement among managers received substantial support (44.8% agreement), alongside recognition of the necessity for information sharing among departmental managers. The results also highlighted a prevailing focus on quality strategies within hotels, with 47.8% of respondents agreeing that their establishments prioritize quality over quantity.